Effectiveness of a multicomponent safe surgery intervention on improving surgical quality in Tanzania's Lake Zone: protocol for a quasi-experimental study. Issue 10 (7th October 2019) - Alidina, Shehnaz; Kuchukhidze, Salome; Menon, Gopal; Citron, Isabelle; Lama, Tenzing N; Meara, John; Barash, David; Hellar, Augustino; Kapologwe, Ntuli A; Maina, Erastus; Reynolds, Cheri; Staffa, Steven J; et al.
Abstract : Introduction: Effective, scalable strategies for improving surgical quality are urgently needed in low-income and middle-income countries; however, there is a dearth of evidence about what strategies are most effective. This study aims to evaluate the effectiveness of Safe Surgery 2020, a multicomponent intervention focused on strengthening five areas: leadership and teamwork, safe surgical and anaesthesia practices, sterilisation, data quality and infrastructure to improve surgical quality in Tanzania. We hypothesise that Safe Surgery 2020 will (1) increase adherence to surgical quality processes around safety, teamwork and communication and data quality in the short term and (2) reduce complications from surgical site infections, postoperative sepsis and maternal sepsis in the medium term. Methods and analysis: Our design is a prospective, longitudinal, quasi-experimental study with 10 intervention and 10 control facilities in Tanzania's Lake Zone. Participants will be surgical providers, surgical patients and postnatal inpatients at study facilities. Trained Tanzanian medical data collectors will collect data over a 3-month preintervention and postintervention period. Adherence to safety as well as teamwork and communication processes will be measured through direct observation in the operating room. Surgical site infections, postoperative sepsis and maternal sepsis will be identified prospectively through daily surveillance and completeness of their patient files, retrospectively, through the chart review. We will use difference-in-differences to analyse the impact of the Safe Surgery 2020 intervention on surgical quality processes and complications. We will use interviews with leadership and surgical team members in intervention facilities to illuminate the factors that facilitate higher performance. Ethics and dissemination: The study has received ethical approval from Harvard Medical School and Tanzania's National Institute for Medical Research. We will report results in peer-reviewed publications and conference presentations. If effective, the Safe Surgery 2020 intervention could be a promising approach to improve surgical quality in Tanzania's Lake Zone region and other similar contexts.